Bone resorption acceleration and calcium reabsorption impairment in a Thai population with high cadmium exposure - Nambunmee K. (2014)
Some residents of the Mae Sot district in Thailand have suffered long-term exposure to elevated dietary levels of cadmium. To test the hypothesis that chronic dietary cadmium exposure can cause imbalance in calcium dynamics and accelerate bone resorption, a group of these residents (156 men and 256 women aged≥50) were selected on the basis of previous records of elevated urinary cadmium and tested for urinary and blood cadmium, bone formation and resorption markers, and the renal tubular dysfunction markers. Both genders had high levels of blood and urinary cadmium and high urinary levels of the markers for renal dysfunction and bone resorption in a doseresponse relationship to urinary cadmium. The excretion of bone resorption markers was positively correlated to the ratio of excreted calcium and urinary cadmium. The results of a multivariate regression analysis indicated that bone resorption was accelerated by impaired calcium reabsorption in renal tubules. © 2010 Informa UK Ltd.